Analisis Kebutuhan Awal Pengembangan Media Interaktif Berbasis Deep Learning untuk Hasil Belajar IPAS Siswa SD - Hilmiyatul Faizah; Ifa Seftia Rakhma Widiyanti; Sita Isna Malyuna; Faizah, Hilmiyatul (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2026)
This study aims to analyze the initial needs for developing interactive media based on deep learning to improve the learning outcomes of fifth-grade students of SDN Guwoterus 02. The study was conducted using a descriptive quantitative approach using four main data sources, namely learning observation results, teacher interviews, student needs questionnaires, and student pretest scores. Observations show that the learning process is still dominated by lecture methods, the use of media is limited to worksheets (LKS) books, and there is minimal variation in motivational strategies. The results of teacher interviews confirm the limited time and skills in using digital media. The student needs questionnaire shows that 84.2% of students find it easier to understand the material with visual support and 89.5% want technology-based learning media. The pretest results of 19 students on the human respiratory system material showed an average score of 63.68 where only 47.4% of students achieved the Learning Objective Achievement Criteria (KKTP) of 70, while 52.6% were still below completeness. Significant heterogeneity in initial abilities (range 30-90) indicates the need for differentiation in media design. Each empirical finding is explicitly mapped to the needs of media features based on three principles of deep learning (mindful learning, meaningful learning, and joyful learning), in line with the principles of the Independent Curriculum.